Penerapan Metode Pengembangan Sistem Extreme Programing (XP) Pada Aplikasi Presensi Karyawan dengan QR Code - Fazrin, Qubaila Ega; Lisnawati, Tuti; Nurhayati, Sri; Satya, Juli Budi; Alamsyah, Dedy (Forum Kerjasama Pendidikan Tinggi, 2021)
Attendance is the process of recording and managing attendance data that is carried out daily during working hours at each company. Errors in recording employee attendance greatly affect employee earnings. So, the validity of the recording is needed. The attendance recording system manually is error-prone and its recapitulation takes a long time. To overcome this, it is necessary to develop an attendance system that can be done quickly and produce valid reports regarding the time of entry and exit. In this study, a presence application will be developed using QR Code scanning by applying the Extreme Programming (XP) method. The extreme programming (XP) method offers stages in a relatively short time. Based on black box testing, the generated QR Code presence application is in accordance with user needs with a functionality test value of 100%